The Influence of Profitability and Leverage on Corporate Social Responsibility Disclosure - Kapitan, Valendra Smaut; Ikram, Syafrizal (Journal of Accounting Auditing and Business, 2019)
This study aims to examine the influence of profitability and leverage on corporate social responsibility disclosure. The study was conducted in companies listed in Indonesia Stock Exchange. Profitability and leverage were treated as independent variables, while disclosure of corporate social responsibility is the dependent variable. The research method was used in this research is a verificative approach. The population in this study is the companies listed in Indonesia Stock Exchange. Sample of the study is the companies included as a member of LQ 45 index for period 2013-2015.  Total listed companies were involved in this study is 67 companies. The sampling technique used in this study is nonprobability sampling with the purposive sampling method. The data analysis used in this study is multiple linear regression analysis at a significance level of 5%. The statistical program was used in analyzing data is Eviews version 8. The results showed that profitability influences corporate social responsibility disclosure. However, leverage does not influence corporate social responsibility disclosure. Simultaneously, profitability and leverage influence corporate social responsibility disclosure